Dane County water recreation study, 2010-2013 - Trechter, David; Hadley, Shelly (My University, 2014)
This report has summarized the results of three connected surveys that collectively were designed to estimate the economic impact of selected water recreation activities on the Dane County economy. In Phase 1, we focused on quantifying the frequency with which Dane County residents engage in recreational activities on or near county lakes and streams. In Phase 2, we measured the proportion of Dane County water recreation participants who live inside and outside the county. In Phase 3, we quantified the amount those who use Dane County water resources for motor boating and fishing from a boat spend in pursuit of their recreational activities. Information drawn from all three phases of the study were used to estimate the overall economic impact of these two recreational activities on the Dane County economy. The three parts of the survey were carried out over three successive years because budgetary limitations made it impractical to conduct them all in one year. The survey period coincided with a long, slow recovery from a sharp economic downturn that saw households become very conscious of their spending. Because recreational spending is highly discretionary, it is likely that the estimates included in this report somewhat conservative.
66 p.
Keywords: Recreation areas--Public use-- Wisconsin--Dane County; Water resources development-- Wisconsin--Dane County; Outdoor recreation--Economic aspects--Wisconsin--Dane County